Ubaldo Castagnoli: on the Graphic and Historical Traces of an Exponent of Gruppo 7 (diségno, 2022)
In 1926, a group of seven friends who studied at the Regio Istituto tecnico superiore of Milan –made up of Ubaldo Castagnoli, Luigi Figini, Gino Pollini, Guido Frette, Sebastiano Larco, Carlo Enrico Rava and Giuseppe Terragni– decided to found Gruppo 7. Between 1926 and 1927, the seven young architects published some articles in the journal Rassegna Italiana that are still considered today as one of the founding moments of the new Italian architecture. Ubaldo Castagnoli left the group almost immediately, being replaced by Adalberto Libera and, for this reason, his name disappears from the history of architecture books. The career of this professional developed within one of the most important companies in the country, STIPEL, the Piedmontese and Lombard interregional telephone company (which in 1964 was incorporated into the SIP), with the role of Central Director at the disposal of the General Management of real estate affairs. He also had a long professional relationship with Luigi Einaudi, before and while he was President of the Republic. The work presented below aims to continue the research recently inaugurated on this figure, that is still not adequately investigated, in order to deepen the role of the cultural debate of those years on his vast professional activity, working with the methods and techniques of the disciplines of representation.
Keywords: Gruppo 7; BIM; STIPEL; Archives and Atlases; graphic analysis